2008
DOI: 10.1021/ja805543p
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Li2FeSiO4

Abstract: A large-scale lithium-ion battery is the key technology toward a greener society. A lithium iron silicate system is rapidly attracting much attention as the new important developmental platform of cathode material with abundant elements and possible multielectron reactions. The hitherto unsolved crystal structure of the typical composition Li2FeSiO4 has now been determined using high-resolution synchrotron X-ray diffraction and electron diffraction experiments. The structure has a 2 times larger superlattice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
183
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(213 citation statements)
references
References 9 publications
(12 reference statements)
28
183
1
1
Order By: Relevance
“…Again, this is an indication of the expected decrease in cell volume. There are also in this case some small impurity peaks that could not be identified and that do not match either Mn 3 Figure 3) and PnLiNaMnSiO 4 (Figure 4), the Rietveld refinement of PnLi 2 MnSiO 4 shown in Figure 5 assumed atomic positions fixed at GGA ab initio DFT values (Table 2), while refining only the cell parameters. In this case, however, the Rietveld model giving best agreement with the observed XRD pattern required inclusion of a bimodal distribution of crystallite sizes for PnLi 2 MnSiO 4 .…”
Section: Electrochemical Testing Of Battery Performancementioning
confidence: 99%
“…Again, this is an indication of the expected decrease in cell volume. There are also in this case some small impurity peaks that could not be identified and that do not match either Mn 3 Figure 3) and PnLiNaMnSiO 4 (Figure 4), the Rietveld refinement of PnLi 2 MnSiO 4 shown in Figure 5 assumed atomic positions fixed at GGA ab initio DFT values (Table 2), while refining only the cell parameters. In this case, however, the Rietveld model giving best agreement with the observed XRD pattern required inclusion of a bimodal distribution of crystallite sizes for PnLi 2 MnSiO 4 .…”
Section: Electrochemical Testing Of Battery Performancementioning
confidence: 99%
“…Fe, Mn or Co have typically been utilised, with more attention recently devoted to Li2FeSiO4 structures, due in part to reasons of safety and cost. The structure of Li2FeSiO4 has been a focus of a number of recent studies owing to its rich display of polymorphism [494][495][496][497][498][499], where a number of different polymorphs, designated as βI, βII, γ0, γII and γs (see Fig. 35), have been identified and account for an experimental variation in the electrochemical performance of Li2FeSiO4 cathodes [498][499][500].…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 99%
“…In this β-structure, chains of LiO 4 tetrahedra run along the a̲ direction parallel to chains of alternating FeO 4 and SiO 4 tetrahedra. Nishimura et al 5 reported the structure of Li 2 FeSiO 4 prepared at 800°C and designated by these authors as γ s (space group P2 1 ). It differs from the other γ structures in that there are no edge sharing trimers of tetrahedra; instead one set of LiO 4 tetrahedra are arranged in edge sharing pairs with FeO 4 tetrahedra, while the other set of LiO 4 tetrahedra forms edge sharing pairs with itself.…”
Section: ■ Introductionmentioning
confidence: 99%